Have the UK Pediatric Trauma Protocols resulted in a reduction in chest computed tomography imaging for children presenting with major blunt trauma? - Samantha Negus; Omar Bouamra; Damian Roland (Journal of the American College of Emergency Physicians Open)
Abstract Objectives To observe variation in imaging requests after publication of the Royal College of Radiologists UK Paediatric Trauma Protocols in 2014, recommending limited use of thoracic computed tomography (CT) to appropriately clinically risk stratified children. Method A retrospective observational study using data from the Trauma Audit & Research Network in the United Kingdom, for children (0–16 years of age) for the years 2012–2021. Percentages were calculated to facilitate comparison between year groups (under 1 year of age, 1–10 years of age, 11–15 years of age), and CT imaging categories reviewed: (1) whole‐body CT (WBCT); (2) abdominopelvic CT (CTAP) with chest radiograph (CXR); (3) chest, abdomen, and pelvic CT (CTCAP) with CXR; (4) CTCAP without CXR; and (5) other imaging. Results Increased use of the recommended protocol (CXR with CTAP) was observed after guidance publication but was not sustained: infants under 1 year old, 0.0% in 2012, 7% in 2017, 0.0% in 2021; 1–10‐year‐olds, 4% in 2012, 13.9% in 2017, 5.5% in 2021; 11–15‐year‐olds, 7.1% in 2012, 10.2% in 2017, 6.6% in 2021. Requests for WBCT increased from 2012–2021 (all age groups, 2.4%, 2012, to 5.3%, 2021) and requests for CTCAP were consistently at a higher level than that of the recommended protocol. Conclusion The increased use of CXR with CTAP after publication of the guidelines, was not sustained with a decreasing trend observed from ∼2017, raising concern for the ionizing radiation burden in this population.